Cerebral Venous Thrombosis: A Mimic of Brain Metastases in Colorectal Cancer Associated with a Better Prognosis - Nida Iqbal; Atul Sharma (Case Reports in Oncological Medicine)
Malignancy is known to be one of the predisposing factors of cerebral venous thrombosis (CVT) due to its hypercoagulable state. CVT is a rare disorder which can lead to frequent misdiagnoses of brain metastases in such cases. We report here the case of a 35-year-old female with metastatic colon adenocarcinoma presenting with sudden neurological symptoms. Brain MRI and magnetic resonance venography confirmed the presence of CVT. She was treated with low molecular weight heparin followed by warfarin. She recovered and is doing well on warfarin after 5 months of diagnosis of CVT. CVT should be strongly suspected as a cause of neurological dysfunction in any case of disseminated malignancy including colon adenocarcinoma. Rapid diagnosis and initiation of therapy should be considered because of its favourable outcome.